Optimization of pigment production by Rhodotorula minuta URM 5197 and Rhodotorula mucilaginosa URM 7409 using yellow passion fruit peel (Passiflora edulis) (Research, Society and Development, 2021)
The objective of this work was to optimize the production of pigments by Rhodotorula minuta and Rhodotorula mucilaginosa through submerged fermentation, using yellow passion fruit peel (Passiflora edulis), as the only substrate. The independent variables evaluated to optimize were: yellow passion fruit peel (YPFP), in grams (g) as culture medium, pH and fermentation time, in days. The study of pigment production and its optimization was carried out using the Doehlert matrix, with fifteen experimental conditions, of which thirteen had different combinations and two repeated the central point. The fixed variables were 30ºC and 150 rpm. Data analysis was performed using the Statistica software version 10.0. The largest amount of total pigments and total carotenoids produced by R. minuta was 28±0.01 mg/L and 72.8±0.026 µg/g, respectively; while for R. mucilaginosa the production of total pigments was 37±0.002 mg/L and total carotenoids 236.8±0.013 µg/g. The optimum production point of total pigments for R. minuta was 2.3g of YPFP, pH 6.5 and 5 days and for R. mucilaginosa 2.5g of YPFP pH 6 and 5 days. In samples of total pigments, the presence of 0.29mg/L of β-carotene for R. minuta and 0.83 mg/L for R. mucilaginosa was identified. It is possible to conclude that yellow passion fruit peel can be used as a nutrient source for Rhodotorula spp growth and pigment production with total carotenoids and β-carotene in its composition.